-3(c-6)=-3c-

Simple and best practice solution for -3(c-6)=-3c- equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(c-6)=-3c- equation:


-3(c-6)=-3c-

We simplify the equation to the form, which is simple to understand
-3(c-6)=-3c-

Reorder the terms in parentheses
+(-3c+18)=-3c-

Remove unnecessary parentheses
-3c+18=-3c-

We move all terms containing c to the left and all other terms to the right.
-3c+3c=-0-18

We simplify left and right side of the equation.
c=-18

0=-18

The left and right sides are not equal, therefore there is no solution. This equation is invalid.

See similar equations:

| 9x-14=12x-50 | | -14=-1-(4x-3) | | 10+2x=12x+46 | | 88.1-2.3h=72.46 | | 3x+14/5x=31/5 | | 5(4n+2)= | | 5x+1/8=6x+3/8 | | x/28+4x3 | | 37-2(x+8)/4 | | 88.1-2.3h=72.4 | | -10+y+18=-3(5y-7)+5y | | 4(y+7)=3+3y | | -3b+ac=c*c | | -4/5n-6=-22 | | x^2-9x-30= | | 74(x+3)=x | | 4n+6-2n=2(n+9) | | 9x-8=9x+12 | | 1/2x=1/6+1/3 | | 5y+8=3y-20 | | 11x-(4x+6)+26=3x | | -4=x+2-(4x-4) | | m-7(4m+3)=141 | | (2-7i)-(-2+5i)= | | 622=x^2 | | 5x+8x-4x=0 | | -3b+ac=c | | 10a+5a=-15 | | -9v-4=2v^2 | | -4+2/3=2n+1/3+n/3 | | -5x(x+4)-1=-16 | | 4-x/-3=13 |

Equations solver categories